HAKIKAT ISLAM DALAM PEMIKIRAN ISLAM MOHAMMED ARKOUN (KONTEKSTUALISASI TRADISI BERPIKIR KRITIS TERHADAP MUSLIM DI INDONESIA) - Nuril Hidayati; Mohammad Zamroni (Bajang Institute, 2025)
Islam in its long historical span is indeed very interesting among Muslim scientists to be dissected through clear exploration using the point of view from which science is emerging and developing as the right horizon of thinking to awaken us, especially in the Islamic world. The need to walk in harmony with established science is the starting point in explaining Islam as a whole. Islam as the focus of attention in Mohammed Arkoun's thinking, on the one hand, plays a very important role because it is a reference for Islam which is critical of existing backwardness and catches up with other backwardness in presenting critical Islam so that with semiotics, which means the theory of signs, it can solve the meaning of Islam itself and show it. modern Islamic thought where the characteristics of the French West can be understood in understanding Arkoun's Islam, including his Islamic thought. The discussion about Mohammed Arkoun itself has the distinction of being library research with various writings raised by Mohammed Arkoun showing his consistency as a critical thinker who is open to inviting thinkers to use modern critical reasoning in utilizing existing knowledge so that they can respond to what is in the world of science. especially Islamic thought